Participation-- who owns it? : enhancing community participation on Bohol Island, Philippines : a thesis presented in partial fulfilment of the requirement for the degree of Master of Philosophy in Development Studies at Massey University - Vos, Robert John (Massey University, 2005)
Community participation has been seen as a means of improving project outcomes with participatory development practices being mainstreamed by most multilateral development agencies. However, 'participation' remains an overused, poorly understood and subjectively defined concept with various partners in the development process concurrently exhibiting different understandings of the concept. A critique of participation also suggests that the rhetoric of participation not only exceeds the practice but that practitioners can use participatory development in an unjust and abusive manner. A problem development organisations in the Philippines face is how to enhance community participation in project communities. Using a case study approach, this research studies a non-government organisation (NGO) and a rural community in the Philippines, partners in implementing two development projects during 1995 - 2003. Research on Bohol during June - July 2004 sought to understand the factors which influenced the willingness and ability of community members to participate in the projects, and the strategies used by the NGO to enhance community participation. This research finds that project participation was enhanced by the community's social cohesion, the NGO's authentic planning and implementation with the community, and the project personnel's respectful and trusting relationships with community members. Similarly, the manner in which project components explicitly met felt need, the enthusiasm generated by the NGO, and the high degree of community ownership of the projects, led to community participation. In contrast, community conflict, the community's negative experience of historical events, selective participation, and the high perceived costs of participation led to non-participation.
Keywords: Community development, Philippines; Bohol Island, Philippines; Rural development, Philippines; Community participation